Salt Tolerance studies: Effect of Soil Salinity on the Growth and Chemical Composition of Plants- Part I - Mehta, B V; Desai, R S (Journal of Soil and Water Conservation, 2022)
Success in irrigated agriculture de- pends latgely upon favourable condi- tions of soil and water. One of the hazards of irrigation  is the tendency of salts contained in the water to accumulate in the soil. The salt aceunutlation in irrigated soils arises not only frotn irrigation water but also from pre-existing deposits in the subsoil. An important factot to be considered in irrigated agriculture is the effect of salts on the growth of crops, as it may not be eco- nomically feasible to maintain low salinity because of saline irrigation water, high water-table or low permeability of the soil. Magistad ct al.12 Bernstein et al.l, Gauch and wadleigh3, Hall et al.4, Shive17, Hayward ct al.6, Eaton2, Livingstonll, Wadleigh and Ayers19, and Haward and Spurr8 have shown that growth inhibition accompanying in- creasing concentrations is virtually linear with the increase in osmotic pressure of the substrate above a particular value. There is also experimental evidence presented by Wadleigh et al.21, Murphy15, Harris et al.5 and U.S. Salinity Laboratory workers18 that different species of plants vary considerably in their response to the increased osmotic pres- sure resulting out of saline conditions in the soil. A knowledge of salt tolerance of crops is, therefore, essential to obtain maximum productivity on a saline soil. It is equally important to know the chemical composition of crops grown under such saline conditions. The present work aims at the study of growth and composition of some common crops grown in goradu soil under saline conditions. In this part only the growth studies are presented.